Prevalence and awareness of osteopenia in perimenopausal women in Navi Mumbai, Maharashtra, India - Dodeja, Ajay; Makhija, Anushka; Rane, Ashita; Dodeja, Meeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Osteopenia is considered as precursor of osteoporosis. Osteoporosis is a major public health problem associated with substantial morbidity and socio-economic burden worldwide. Osteopenia occurs more frequently in most menopausal women. Early detection of the same can be beneficial to control prevalence of osteoporosis and also to reduce the fracture rates. Methods: A cross-sectional quantitative study using DEXA (Dual Energy X-ray Absorptiometry) was conducted on 80 women. A self-structured questionnaire was used to evaluate the level of awareness among the study subjects. The data was analyzed using statistical tests such as Chi-Square test for association. The level of significance was set at 5%. Results: The prevalence of osteopenia in the studied population was 63.75%. The mean age was recorded to be 40.35 years. The mean age of women with menopause in this study is 50.62 years. Out of the 51(63.75%) women diagnosed with osteopenia, 5.9% were underweight, 33.3% were normal and 49% were obese. Of the diseased, 37.3% experienced adequate amount sunlight exposure required while 62.7% did not. Out of the 80 women interviewed 43.75% were aware about osteopenia, its causes and complications; which 56.25% were unaware about the same. Conclusions: Women were screened for osteopenia with the help of DEXA scan according to the (World Health Organization) WHO, T-Score criteria-which may go undiagnosed otherwise and may experience the risk and complications of osteoporosis.